Curated Databases - Buneman, Peter; Cheney, James; Wang-Chiew Tan; Stijn Vansummeren (My University, 2011)
Curated databases are databases that are populated and updated with a great deal of human eﬀort. Most reference works that one traditionally found on the reference shelves of libraries – dictionaries, encyclopedias, gazetteers etc. – are now curated databases. Since it is now easy to publish databases on the web, there has been an explosion in the number of new curated databases used in scientiﬁc research. The value of curated databases lies in the organization and the quality of the data they contain. Like the paper reference works they have replaced, they usually represent the eﬀorts of a dedicated group of people to produce a deﬁnitive description of some subject area. Curated databases present a number of challenges for database research. The topics of annotation, provenance, and citation are central, because curated databases are heavily cross-referenced with, and include data from, other databases, and much of the work of a curator is annotating existing data. Evolution of structure is important because these databases often evolve from semistructured representations, and because they have to accommodate new scientiﬁc discoveries. Much of the work in these areas is in its infancy, but it is beginning to provide suggest new research for both theory and practice. We discuss some of this research and emphasize the need to ﬁnd appropriate models of the processes associated with curated databases.